New project sheds light on the worldwide use of solitary confinement - Mølgaard, Andrea (Torture Journal, 2024)
The ‘Mapping Solitary Confinement’ project, launched in early 2024 by Dr Sharon Shalev and collaborators, aims to shed light on the global use of solitary confinement - also known as ’isolation’ or ‘segregation’. The project, a collaborative effort involving contributors from all over the world, is structured around relevant human rights standards, in particular the UN Special Rapporteur on Torture’s recommendations and the United Nations Standard Minimum Rules for the Treatment of Prisoners also known as the ‘Mandela Rules’ (UN, 2011; UN General Assembly, 2015). The project includes comprehensive reports on national practices from 57 jurisdictions within 42 countries across six continents, compiled by a wide network of volunteers all over the world.